2003
DOI: 10.1053/jlts.2003.50142
|View full text |Cite
|
Sign up to set email alerts
|

Carriage of methicillin-resistant Staphylococcus aureus is associated with an increased risk of infection after liver transplantation

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) is an important cause of sepsis in patients with cirrhosis and after liver transplantation. The association between nasal carriage of MRSA and sepsis in these patients is unclear. The goal of this study was to investigate the relationship between MRSA carriage before liver transplantation and subsequent sepsis after transplantation. This was a retrospective study of 374 consecutive adults who underwent orthotopic liver transplantation between 1998 and 2001 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
57
0
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 11 publications
6
57
0
3
Order By: Relevance
“…These data were exclusively for patients who had undergone liver transplantation. We found that pretransplant MRSA carriage in liver transplant recipients (15,19,23 (16,17,27,36) with pertinent data. The Freitas et al (16) study had zero events in both arms and was not pooled.…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations
“…These data were exclusively for patients who had undergone liver transplantation. We found that pretransplant MRSA carriage in liver transplant recipients (15,19,23 (16,17,27,36) with pertinent data. The Freitas et al (16) study had zero events in both arms and was not pooled.…”
Section: Resultsmentioning
confidence: 77%
“…The pooled effects and sensitivity analyses are displayed in Table 2. Before transplantation, the estimated MRSA colonization was 8.5% (95% CI 3.2-15.8; effect derived from nine studies (13)(14)(15)19,(21)(22)(23)29,33) in 2885 patients (t 2 ¼ 0.107) and VRE colonization was 11.9% (95% CI 6.8-18.2; effect derived from eight studies (14,17,18,20,24,25,35,36) that included 1381 patients (t 2 ¼ 0.060). Effects referred to liver patients exclusively for VRE, whereas for MRSA two out of nine eligible studies reported data on kidney and/or pancreas and lung patients (13,33).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Infecções causadas por cepas resistentes de Staphylococcus aureus não se caracterizam como fenômeno isolado ou exclusivo de países de baixa renda, uma vez que se observa número crescente de estudos relacionados à epidemiologia deste microorganismo em centros que comportam pacientes imunocomprometidos (Lizioli et al, 2003), que sofreram intervenção cirúrgica , que foram transplantados (Desai et al, 2003) ou que são portadores de queimaduras graves (Fuchs et al, 2002). Notase ainda, uma grande preocupação da comunidade científica em estabelecer possíveis alternativas relacionadas ao controle e prevenção da colonização por MRSA (Methicillin-Resistant Staphylococcus aureus) em hospitais de todo o mundo, ressaltando a gravidade e a necessidade de busca de soluções para este problema Rohr et al, 2003).…”
Section: Introductionunclassified